Lupenone preserves T cell activity by recovery of CD40L expression and protection from cytotoxicity due to methamphetamine exposure - Hyun-Su Lee; Eun-Nam Kim; Gil-Saeng Jeong (PLoS ONE, 2025)
Methamphetamine (METH) is one of the most highly compulsive drugs in the world and has become a major public health problem over the last two decades. Exposure to METH has been investigated to cause neuronal toxicity but little is known about the effect of METH on the activity and toxicity of T lymphocytes. Lupenone has been reported to possess anti-diabetic, anti-inflammatory and anti-apoptotic effects but little is known about whether lupenone has a protective effect on T cell activation in METH-exposed cells. We evaluated the cytotoxicity and cytoprotective effects of lupenone in METH-stimulated Jurkat T cells. Results from the inhibitor assay using CD40L blocking antibodies revealed that this was due to enhanced CD40L expression on the T cells by pre-treatment with lupenone. Pre-treatment with lupenone significantly reduces METH-induced toxicity by restoring the expression of anti-apoptotic proteins in activated T cells. The protective effects of lupenone on activated T cells exposed to METH were associated with the prevention of MAPK and PI3K/Akt/mTOR pathways. These data suggest lupenone protected T cell activity by elevating CD40L expression and cell viability in cells exposed to methamphetamine. Our data showed that lupenone treatment recovered the expression of IL-2 and CD69 in METH-exposed cells.